المسرح التعليمي في المدرسة الجزائرية بين المتعة واستشراف الوعي – نماذج من الطور الثانوي - عثمان, ميهوبي; احلام, بن الشيخ (جامعة الوادي - University of Eloued, 2021)
ملخص: يلعب المسرح التعليمي دورا هاما في تنمية القدرات العلمية والمواهب الفذّة لدى الناشئة، وعلى اعتبار أن التلميذ هو حجر الزاوية في العملية التعليمية التعلمية، حظي المسرح التعليمي بمكانة رفيعة فيها، فهو يعمل على بث روح الفرجة والمتعة في نفوس المتعلّمين، مشكّلا في الوقت عينه حركة إصلاحية محمّلة برسائل ذات طابع قيمي أخلاقي، ومن هنا اصطبغ هذا النّوع من المسرح بحِلْيَة الظرف والفكاهة ممزوجا بمعيار الوعي والإصلاح في المدرسة الجزائرية. الكلمات المفتاحية: المسرح التعليمي؛ المدرسة؛ الإصلاح؛ المتعة؛ الوعي. Abstract: The educational theater plays an important role in developing the scientific abilities and the talents of the emerging, and considering that the student is the cornerstone of the educational process. The educational theater has a high position in it, as it works to spread the spirit of relief and pleasure in the hearts of learners. At the same time, it forms a reform movement which is loaded with messages of a moral and ethical nature. Hence, this type of theater is tinged with the sweetness of circumstance and humor mixed with the standard of awareness and reform in the Algerian school. Key words: educational theater; school; reform; joy; awareness. .
Keywords: المسرح التعليمي ; المدرسة ; الإصلاح ; المتعة ; الوعي